Polyaxial versus Uniaxial Volar Locking Plate for Distal Radial Fractures. (April 2014) - Al-Mouazzen, Louay; Chou, Daud Tai Shan; Kyriakopoulos, Georgios; Hambidge, John
Purpose: To compare the penetration of the distal screws in relation to the thickness of the distal metaphysis in the polyaxial versus uniaxial volar locking plates. Methods: Records of 78 patients aged 16 to 79 years who underwent open reduction and internal fixation for distal radial fractures (n=81) were reviewed. All fracture subtypes were included. 20 men and 22 women aged 18 to 79 (mean, 50) years were treated with the uniaxial locking plate, whereas 15 men and 21 women aged 16 to 79 (mean, 51) years were treated with the polyaxial locking plate. The choice of plate was determined by the operating surgeon based on familiarity and perceived advantages of the 2 plates. Penetration of the distal locking screws in relation to the volar-dorsal thickness of the distal radial metaphysis was measured, and the percentage of subchondral bone unsupported by the screws calculated. Results: The mean percentage of unsupported subchondral bone was significantly lower in the polyaxial than uniaxial volar locking plate group (12% vs. 23%, p<0.001). No patient had screw overpenetration. Conclusion: The polyaxial volar locking plate system enabled deeper insertion of distal screws into the subchondral bone, and thus providing better buttress for the fracture fragments.